Factors affecting purchase behaviour of Shariah compliant hotels: a study from Muslim consumers’ perspective - Haque, A. K. M. Ahasanul; Azam, S.M Ferdous; Chowdhury, Naila Anwar (Inderscience Enterprises Ltd., 2019)
The present study is undertaken to examine the effects of various factors on Muslim consumers’ purchase behaviour towards Shariah compliant hotels on the basis of the theory of planned behaviour. The data required for the study has been gathered through the distribution of self-administered questionnaires to Muslim consumers in Kuala Lumpur, Malaysia. The data has been analysed through SPSS and SEM. The findings demonstrate that attitude, subjective norm and perceived behavioural control carry positive effects on Muslim consumers’ purchase intention toward Shariah compliant hotels. Moreover, perceived behavioural control and intention to purchase significantly affect purchase behaviour towards Shariah compliant hotels. The findings of the study will facilitate marketers in terms of creating effective strategies in order to fulfil the needs and wants of Muslim consumers. From an academic viewpoint, the study has opened the door for future researchers to conduct more studies on Shariah-compliant hotels.